Growth, Health, and Gut Microbiota of Female Pacific White Shrimp, Litopenaeus vannamei Broodstock Fed Different Phospholipid Sources - Xiaolong Liang; Xiaolong Luo; Hongxing Lin; Fenglu Han; Jian G. Qin; Liqiao Chen; Chang Xu; Erchao Li (MDPI AG, 2022)
Phospholipids have an important antioxidant effect on animals. The effects of different dietary phospholipid sources on the growth, antioxidant activity, immunity, and gut microbiota of female broodstock of Pacific white shrimp Litopenaeus vannamei were investigated. Four isoproteic and isolipid semi-purified diets containing 4% soybean lecithin (SL), egg yolk lecithin (EL), or krill oil (KO) and a control diet without phospholipid supplementation were fed to female broodstock of L. vannamei (34.7 ± 4.2 g) for 28 days. The growth performance, antioxidative capacity, and innate immunity of the female broodstock fed phospholipid supplemented diets were improved regardless of sources compared with the control shrimp. The effects on growth and antioxidant capacity in female shrimp fed the KO diet were highest. The innate immunity of female shrimp fed the EL and KO diets were significantly higher than shrimp fed the SL diet. Dietary phospholipid supplementation increased gut microbiota diversity and richness, and the Chao1 and ACE values in the KO group were significantly higher than in the control group. The richness of Proteobacteria, Photobacterium, and Vibrio decreased, whereas the richness of Firmicutes and Bacteroidetes increased in the shrimp fed the KO diet compared with the shrimp fed the SL and EL diets. The interactions of gut microbiota in shrimp fed the KO diet were the most complex, and the positive interaction was the largest among all the treatments. The functional genes of gut microbiota in shrimp fed the KO diet were significantly enriched in lipid metabolism and terpenoid/polyketide metabolism pathways. Spearman correlation analysis showed that Fusibacter had significantly positive correlations with antioxidant activity (total antioxidant capacity, superoxide dismutase, glutathione peroxidase), immune enzyme activity (phenoloxidase and lysozyme), and immune gene expression (C-type lectin 3, Caspase-1). All findings suggest that dietary phospholipids supplementation can improve the growth and health status of female L. vananmei broodstock. Krill oil is more beneficial in improving the antioxidant capacity and innate immunity than other dietary phospholipid sources. Furthermore, krill oil can help establish the intestinal immune barrier by increasing the richness of Fusibacter and promote the growth of female shrimp. Fusibacter may be involved in iron metabolism to improve the antioxidant capacity of female shrimp.